Relationship between vasomotor symptom improvements and quality of life and sleep outcomes in menopausal women treated with oral, combined 17β-estradiol/progesterone. Issue 6 (June 2019) - Mirkin, Sebastian; Graham, Shelli; Revicki, Dennis A.; Bender, Randall H.; Bernick, Brian; Constantine, Ginger D.
Abstract: Objective: To characterize the impact of TX-001HR on the relationship between vasomotor symptom (VMS) improvement and quality of life and sleep. Methods: REPLENISH (NCT01942668) was a phase 3, randomized, double-blind, placebo-controlled, multicenter trial, which evaluated four daily doses of 17β-estradiol and progesterone (E2/P4) combined in a single, oral, softgel capsule in postmenopausal women (40-65 years) with a uterus and moderate to severe VMS (≥7/day or ≥50/week). In post hoc analyses, growth models were used to examine relationships between linear changes in VMS frequency and severity over 12 weeks and changes from baseline in the Menopause-Specific Quality of Life (MENQOL; total score and VMS domain) and the Medical Outcomes Study-Sleep (total score, sleep problems indices I and II) questionnaire outcomes at 12 weeks with treatment compared with placebo. Results: Outcomes with all four E2/P4 doses were combined (n = 591) and compared with placebo (n = 135). In all 5 growth models, the effects of TX-001HR on MENQOL total score and vasomotor domain were significantly associated with changes in VMS frequency and severity observed over 12 weeks (all, P < 0.001). Treatment-mediated effects on MENQOL via VMS frequency and severity models were significant. Similar results were found with Medical Outcomes Study-Sleep total score and sleep problems indices. Conclusions: TX-001HR improvements in quality of life and sleep outcomes are associated with and may be mediated through improvements in VMS frequency and severity.